Handphone sebagai Inspirasi dalam Berkarya Still Life - Sari Dewi Kuncoroputri; Belinda Sukapura Dewi; Muhamad Ali Rahim (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
At present, to save time and energy when doing a job, communicating, obtaining daily needs (such as food and drinks) and so on, technology is the solution, with one of its rapid developments being smartphones as a service provider support community life. It is this device that inspires artists to make artworks. The purpose of this artwork is to convey the artist's ideas through still life works of art. The method used is descriptive qualitative method. The data collection technique applied was a literature study (data collection). The results displayed are still life style two-dimensional (2D) paintings made in 2023 with the main objects being carried are food, drinks, smartphones, and things related to the main object.